Dr. Valerie Nur and Prof. Dr. Joël Glasman on artisanal knowledge in Niger from a mobility perspective - Nur, Valerie; Glasman, Joël (Cluster Conversations, 2024)
During this episode Cluster fellow Valerie Nur talks with her fellowship host Prof. Dr. Joël Glasman (Chair of African History at the University of Bayreuth) about her research on the topic of artisanal knowledge and skills from a mobility perspective. Artisans in Niger often offer their services on the road and, in doing so, rely on a broad kinship network during their travels, within which knowledge, practices, and materials are exchanged, modified, and enhanced. By looking beyond single workshops and individual skills, she understands artisanal skill as a shared dynamic practice and places and routes of learning and exchange as hubs of technology and knowledge transfer over long distances. During her research, Nur aims to conceptualize craft as an epistemology of an exclusive professional community.